Creating Contexts for Adult Motivation for Foreign Language Learning and Acquisition - Karapetyan, Mariana (Armenian Folia Anglistika, 2006)
While developing foreign language teaching methods for adult students aged 17-20, it is necessary to take into account not only teaching and learning related issues, but also a number of principles which are connected with adult teaching. The article discusses a set of issues connected with foreign language teaching methodology with view of not only the specific features of the foreign language teaching methods for adults but also the theories that attach importance to the factor of emotions in the teaching process. The article attempts to combine a foreign language teaching and learning with the theory of game. The aim of the research is to reveal how games contribute to the improvement of foreign language teaching and learning.